Hubungan antara Kecerdasan Adversitas dengan Adaptabilitas Karier pada Karyawan BNI Cabang Rengat - Ifani Candra; Jimmi Bernhard; Harri Kurniawan (Psyche 165 Journal, 2021)
This study aims to see the relationship between adversity intelligence and career adaptability of BNI employees of the Rengat branch. The independent variable in this study is adversity intelligence and the dependent variable is career adaptability. The measuring instrument used in this research is the adversity intelligence scale and the career adaptability scale. The sampling technique used in this study was saturated sampling with a total sample size of 35 employees. The validity test uses the Corrected Item-Total Correlation and the reliability test uses the Alpha Cronbach technique. The test results show the validity coefficient on the adversity intelligence scale ranges from 0.326 to 0.732, while the reliability coefficient is 0.915. The results of the validity coefficient on the career adaptability scale ranged from 0.349 to 0.831, while the reliability coefficient was 0.939. Based on the results of data analysis, the correlation coefficient is 0.368 with a significant level of correlation (p) = 0.030 (< 0,05). This means that there is a significant relationship with a positive direction between adversity intelligence and career adaptability of the BNI Rengat branch. So it can be interpreted that the hypothesis in this study is accepted. The effective contribution of the adversity intelligence variable with career adaptability is as much as 14%.